Students’ Perception in Using Daily Activities Diary to Improve Writing Ability of the Tenth-Grade Students of SMA Negeri 1 Mamuju - Rusdi, Jumriah; Dollah, Syarifuddin; Sakkir, Geminastiti (Har Press Indonesia, 2024)
This study analyzed the use of a daily activities diary to improve students' writing ability. The study aimed to determine students' perceptions of using daily activities diary to improve the writing ability of the tenth-grade students of SMA Negeri 1 Mamuju. This study used a quantitative research method with quasi-experimental design. The population of this study was the students of SMA Negeri 1 Mamuju. The samples of this study were students of class X B who used the daily activities diary continuously. The researcher used interviews as the research instrument. The results of this study showed that students' perceptions of using daily activities diary to improve their writing ability were positive perception. This illustrates that the use of a daily activities diary could improve the writing skills of tenth-grade students of SMA Negeri 1 Mamuju.